Operational risk associated with the strategy implementation = Ryzyko operacyjne towarzyszące implementacji strategii - Radomska, Joanna (Zielona Góra: Faculty of Economics and Management Press)
The paper discusses the subject of the strategy implementation and the operational risk that accompanies this stage of the strategic management process. The studies confirmed the existence of a relationship between the effectiveness of the strategy implementation and the operational risk aspects (including internal processes, systems, people and the environment).
Keywords: Zarządzanie strategiczne; wdrażanie strategii; ryzyko operacyjne; Strategic management; strategy implementation; risk